The Affluence of Tanjung Laboh: The Development of Tanjung Laboh E-Tourism Mobile Application. - Zuraida Ibrahim,; Tamil Arasi,; Farah Aqilah Mohd Yani,; Sakinah Balqis Norazman, (Multidisciplinary Applied Research and Innovation, 2023)
In the state of Johor, substantial efforts to create natural tourist products are still insufficient. There is currently less unique promotion in place to successfully promote nature as a tourism commodity. Mobile and wireless technologies have been identified as one of the most attractive areas of technological innovation for enhancing internet applications to tourism in the tourism management arena. In addition, there are previous studies on tourism applications such as Agoda, Trivago but these applications are booking applications and not a personalized-location application. Therefore, this study aims to develop an e-tourism mobile application to promote natural tourism in Tanjung Laboh  area by designing an application that has food and accommodation recommendations and also games that gives knowledge about history in Tanjung Laboh. This research applied the waterfall approach. There are five phases employed, which are requirement, analysis, design, implementation and testing. Hopefully, the personalized-location applications namely “The Affluence of Tanjung Laboh” will attract more people participating in the tourism industry specially in Tanjung Laboh, Batu Pahat, Johor.